Uji Efektivitas Ekstrak Daun Cengkih dan Jintan untuk Menurunkan Intensitas Serangan Penyakit Antraknosa pada Tanaman Cabai Besar - Jimmy Dwi Cahya; Andree Wijaya Setiawan (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Anthracnose disease is one of the diseases in chili plants that can reduce yields by up to 80%. This study aims to determine the effectiveness and optimal concentration of natural fungicides from cloves and cumin in reducing the incidence and intensity of anthracnose disease (Colletotrichum sp.) attack directly on large chili plants in the field. The research was conducted in Sumberejo Village, Ngablak District, Magelang Regency. The study used a completely randomized design (CRD) with eight treatments and four replications. The extract treatments used clove leaves and cumin leaves with concentrations of 1%, 2%, and 3%, and no treatment and synthetic fungicides. The variables observed in this study were disease incidence, intensity of attack, and total fruit weight at harvest. The use of pesticides in the study showed significant differences from that of the control. The best natural fungicides for disease incidence in this study were CK3 (1,79%) and JK3 (2,94%), while the best natural fungicide treatments for attack intensity in this study were CK3 (11,25%) and JK3 (16,25%). Applying clove and cumin leaf fungicides to plants does not reduce crop yields.